Silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte and preparation method thereof
Through the oxide-type porous ceramic composite solid electrolyte derived from silk filament hydrogel, the problems of low ionic conductivity and poor electrochemical stability of flexible polymer solid lithium batteries are solved, and the flexibility of high energy density and long-term cycle stability is achieved Solid-state lithium battery.
Patent Information
- Application Number
- CN202111483517.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-12-07
AI Technical Summary
Existing flexible polymer solid-state lithium batteries have limited their application in wearable electronic products due to problems such as low ionic conductivity, poor electrochemical stability and lithium metal side reactions.
Using oxide-type porous ceramic composite solid electrolyte derived from silk hydrogel, a 3D porous oxide ceramic frame is prepared by ultrasonic treatment and calcination. It is used as a filler for flexible composite solid electrolytes, optimizes the morphology and structure of the ceramic filler and provides continuous Li+ Transfer paths and reduce ceramic/polymer interface resistance.
The ionic conductivity and electrochemical stability of flexible all-solid lithium batteries are improved, high reversible capacity and long-term cycle stability are achieved, and the safety performance of the battery is enhanced.
Smart Images

Figure CN115249836B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an energy storage functional material, in particular to an oxide-type porous ceramic composite solid electrolyte derived from a silk fibroin hydrogel and a preparation method thereof, belonging to the technical field of preparation of energy storage functional materials. Background Art
[0002] In recent years, with the vigorous development of wearable electronic products such as bendable screens, smart bracelets, and AR glasses, flexibility and wearability are becoming the development trend of portable electronic devices. As one of the most popular secondary batteries in recent years, lithium-ion batteries are very likely to be used as flexible energy storage devices to provide stable and continuous power for wearable electronic products. However, due to the use of organic flammable liquid electrolytes, current commercial lithium-ion batteries have the defects of insufficient energy density and low safety, which limits their use as flexible energy storage devices and cannot match wearable electronic products.
[0003] Compared with traditional liquid lithium-ion batteries, flexible all-solid-state lithium batteries have attracted much attention due to their ultra-high energy density and good safety performance. Among them, solid electrolytes, as the core component of flexible all-solid-state lithium batteries, directly determine the overall performance of the battery. At present, common flexible solid electrolytes are made of a mixture of polymer matrix and conductive lithium salts. They are easy to prepare and have good mechanical flexibility. However, this type of polymer solid electrolyte faces the problem of low ionic conductivity (10 -6 -10 -8 S cm -1 ), narrow electrochemical stability window, and side reactions with lithium metal, resulting in poor overall performance of all-solid-state lithium batteries.
[0004] An effective solution to the problems of flexible polymer solid electrolytes is to construct a composite system by dispersing oxide nano-ceramic particles with high ionic conductivity as active fillers in a polymer matrix. Oxide nano-ceramic particles can not only improve the mechanical strength and electrochemical stability of polymer solid electrolytes, but also improve ionic conductivity by reducing polymer crystallinity. However, due to the huge difference in surface energy between inorganic ceramics and organic polymers, ceramic fillers are prone to aggregation in the polymer matrix, which seriously affects ion transport. In addition, since the nano-ceramic particles are isolated from each other, it is impossible to form a continuous Li + transport path, reducing the overall ionic conductivity of the solid electrolyte. Summary of the invention
[0005] The invention provides a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, which can be used as an electrolyte material for a solid-state lithium battery.
[0006] The present invention also provides a method for preparing the oxide-type porous ceramic composite solid electrolyte derived from the silk fibroin hydrogel.
[0007] The technical solution adopted by the present invention to solve the technical problem is:
[0008] A silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte and a preparation method thereof, the method comprising the following steps:
[0009] S1. Preparation of "Silk Fibroin-Oxide Ceramic Precursor Salt" Hydrogel:
[0010] dissolving an oxide ceramic precursor salt in water to obtain a ceramic precursor salt solution;
[0011] Then, the silk fibroin is dissolved in a ceramic precursor salt solution to obtain a "silk fibroin-oxide ceramic precursor salt" aqueous solution with a silk fibroin mass content of 3%-10%, and the solution is subjected to ultrasonic treatment and allowed to stand to obtain a "silk fibroin-oxide ceramic precursor salt" hydrogel;
[0012] S2. Preparation of oxide-type porous ceramics: The "silk fibroin-oxide ceramic precursor salt" hydrogel obtained in S1 is dried to obtain a dry gel, which is then calcined in air to obtain an oxide-type porous ceramic;
[0013] S3. Preparation of oxide-type porous ceramic composite solid electrolyte:
[0014] The polymer that can be used as a solid electrolyte and the conductive lithium salt are vacuum dried in a temperature range below their respective melting points for later use;
[0015] Then the polymer and the conductive lithium salt are dissolved in acetonitrile, and the oxide-type porous ceramic obtained by S2 is added, stirred and dispersed evenly to form a solid electrolyte mixed solution; the weight ratio of the polymer to the conductive lithium salt is 2 to 4:1; the oxide-type porous ceramic accounts for 5% to 30% of the total weight of the polymer, the conductive lithium salt and the oxide-type porous ceramic;
[0016] Finally, the solid electrolyte mixed solution is coated on the mold, and after the acetonitrile is completely volatilized, the mold is demoulded and vacuum dried to obtain an oxide-type porous ceramic composite solid electrolyte.
[0017] In view of the problems existing in the current composite solid electrolytes, the present invention proposes a method for preparing a silk hydrogel-derived oxide-type porous ceramic composite solid electrolyte, that is, using silk hydrogel as a derivative template to prepare a 3D porous oxide ceramic framework, which is used as a filler for a flexible composite solid electrolyte. By optimizing the morphology and structure of the oxide ceramic filler and constructing a 3D ceramic framework in a polymer matrix, it is possible to avoid the agglomeration of the ceramic filler to a certain extent and to provide Li + Provides a fast and continuous transmission path.
[0018] The invention is simple to prepare and can be mass-produced. The obtained oxide porous ceramic framework has a 3D mesh-like interconnected ion-conducting path, which can not only avoid the mutual agglomeration of ceramic fillers, but also can provide Li + In addition, the polymer can penetrate into the porous network of the ceramic framework to form a tight organic polymer / inorganic ceramic interface, thereby reducing the interfacial resistance of the two and further improving Li + The transfer rate at the interface. All-solid-state lithium batteries based on oxide-type porous ceramic composite solid electrolytes also exhibit high reversible capacity and long-term cycle stability.
[0019] Preferably, the ceramic precursor salt in S1 is selected from garnet-type, NASICON-type, perovskite-type or antiperovskite-type ceramic precursor salt, and the content of the ceramic precursor salt in the "silk fibroin-oxide ceramic precursor salt" aqueous solution is 0.04-0.8 mol / L.
[0020] Preferably, the parameters of the ultrasonic treatment in S1 are: ultrasonic power of 200-500 W, ultrasonic time of 5-20 min, and standing time after ultrasonic treatment of 6-48 h.
[0021] Preferably, the drying temperature of the "silk fibroin-oxide ceramic precursor salt" hydrogel in S2 is 80°C±5°C, and the drying time is 24h±4h.
[0022] Preferably, the calcination temperature of the "silk fibroin-oxide ceramic precursor salt" dry gel in S2 is 700-1000°C, and the calcination time is 2h±0.5h.
[0023] Preferably, the oxide-type porous ceramic in S3 accounts for 10% of the total weight of the polymer, the conductive lithium salt and the oxide-type porous ceramic; and the concentration of the polymer in the mixed solution is 0.02-0.1 g / L.
[0024] Preferably, in S3,
[0025] The polymer is selected from a mixture of one or more polymers selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinyl chloride (PVC),
[0026] Conductive lithium salts are selected from lithium halides (LiX, X = F, Cl, Br, I), lithium bis (trifluoromethylsulfonyl) imide (LiTFSI), lithium perchlorate (LiClO 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 )wait.
[0027] Preferably, the vacuum drying temperature of the oxide-type porous ceramic composite solid electrolyte in S3 is 50°C±5°C, and the drying time is 24h±4h.
[0028] Preferably, the preparation method of the silk fibroin is: degumming and refining silk cocoons to obtain pure silk fibroin, dissolving salt to obtain a silk fibroin solution, and centrifuging, dialysis, and freeze-drying to obtain the silk fibroin.
[0029] Preferably, the specific preparation method of silk fibroin in step (1) is:
[0030] Ⅰ. Add 2.5g Na 2 CO 3 The mixture was dissolved in 500 mL of deionized water, and then 10 g of silk cocoons were added. The mixture was degummed in a 98°C water bath for 30 min. The degumming was repeated three times to obtain silk fibroin fibers.
[0031] Ⅱ. Press CaCl 2 :CH 3 CH 2 OH:H 2 The silk fibroin solution was prepared in a molar ratio of O=1:2:8, and then the silk fibroin fibers were placed in the solution and dissolved in a water bath at 75°C for 4 hours to obtain the silk fibroin solution.
[0032] III. The silk fibroin solution was centrifuged and dialyzed for 72 hours to remove impurities and residual metal ions, and then the purified silk fibroin solution was placed in a refrigerator for 24 hours, and finally freeze-dried at -50°C and 40Pa for 72 hours to obtain silk fibroin protein.
[0033] An oxide-type porous ceramic composite solid electrolyte for a flexible solid-state lithium battery. The composite material is prepared by the preparation method.
[0034] The present invention first uses silkworm cocoons as raw materials, extracts and prepares pure silk fibroin by salt dissolution method; then prepares oxide ceramic precursor salt solution, adds silk fibroin thereto, and obtains "silk fibroin-oxide ceramic precursor salt" hydrogel by ultrasound accelerated gelation; then dries the hydrogel and calcines at high temperature to obtain an oxide-type porous ceramic framework derived from the silk fibroin hydrogel; finally, the oxide-type porous ceramic framework is compounded with the "polymer-conductive lithium salt" system to obtain an oxide-type porous ceramic composite solid electrolyte, which can be applied to the energy storage field represented by flexible all-solid-state lithium batteries. The method of the present invention has the following characteristics:
[0035] (1) The present invention is simple to prepare, the reaction conditions are easy to control and implement, and can be produced on a large scale;
[0036] (2) Compared with traditional nanoceramic particle fillers, the oxide-based porous ceramic framework derived from silk hydrogel has a 3D interconnected ion transport network, which can accelerate Li + Migration in solid electrolytes;
[0037] (3) The ultra-loose porous structure of the oxide-type porous ceramic framework and its large specific surface area can promote the "polymer-conductive lithium salt" system to penetrate into the ceramic framework, forming a continuous and tight inorganic ceramic / organic polymer interface, thereby improving the Li + The transfer rate at the interface;
[0038] (4) The obtained oxide-type porous ceramic composite solid electrolyte can be applied to flexible all-solid-state lithium batteries, and has good electrochemical performance and high safety;
[0039] (5) The preparation method of oxide-type porous ceramics derived from silk hydrogel template can be extended to other superporous porous materials, such as porous carbon, foamed metal oxides, and porous metal-organic frameworks. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a scanning electron microscope (SEM) photograph of the oxide-type LLZO porous ceramic prepared in Example 1;
[0041] Figure 2 Surface SEM photos of the oxide-type LALZO porous ceramic composite solid electrolytes with different contents prepared in Example 2 and a cross-sectional SEM photo of the oxide-type LALZO porous ceramic composite solid electrolyte with a content of 10%;
[0042] Figure 3 is the X-ray electron diffraction (XRD) spectrum of the oxide-type LALZO porous ceramic prepared in Example 3;
[0043] Figure 4 are the high magnification transmission electron microscope (HRTEM) photograph and selected area electron diffraction (SAED) spectrum of the oxide-type LALZO porous ceramic prepared in Example 3;
[0044] Figure 5 This is an electrochemical impedance spectrum (EIS) diagram of a stainless steel / solid electrolyte / stainless steel symmetric cell of an oxide-type LLZTO porous ceramic composite solid electrolyte prepared in Example 4;
[0045] Figure 6 1 is a cycle performance diagram of a Li / solid electrolyte / Li symmetric battery of an oxide-type LLZTO porous ceramic composite solid electrolyte prepared in Example 4;
[0046] Figure 7The Li / solid electrolyte / LiFePO of the oxide-type LLTO porous ceramic composite solid electrolyte prepared in Example 5 4 Long-term cycling performance of all-solid-state batteries. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0048] In the present invention, unless otherwise specified, all parts and percentages are by weight, and all equipment and raw materials can be purchased from the market or are commonly used in the industry.
[0049] Example 1
[0050] A method for preparing a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, the method comprising the following specific steps:
[0051] (1) Preparation of silk fibroin:
[0052] Ⅰ. Add 2.5g Na 2 CO 3 The mixture was dissolved in 500 mL of deionized water, and then 10 g of silk cocoons were added. The mixture was degummed in a 98°C water bath for 30 min. The degumming was repeated three times to obtain silk fibroin fibers.
[0053] Ⅱ. Press CaCl 2 :CH 3 CH 2 OH:H 2 The silk fibroin solution was prepared in a molar ratio of O=1:2:8, and then the silk fibroin fibers were placed in the solution and dissolved in a water bath at 75°C for 4 hours to obtain the silk fibroin solution.
[0054] III. The silk fibroin solution was centrifuged and dialyzed for 72 hours to remove impurities and residual metal ions, and then the purified silk fibroin solution was placed in a refrigerator for 24 hours, and finally freeze-dried at -50°C and 40Pa for 72 hours to obtain silk fibroin protein.
[0055] (2) Preparation of “Silk Fibroin-Oxide Ceramic Precursor Salt” Hydrogel:
[0056] Ⅰ. 17.5 mmol LiNO 3 , 7.5 mmol La(NO 3 ) 3 6H 2 O, 5 m mol ZrO(NO 3 ) 3 6H2 O was dissolved in 15 mL of deionized water to obtain the oxide ceramic Li 7 La 3 Zr 2 O 12 (LLZO) precursor salt solution, in order to compensate for the lithium loss in LLZO during subsequent high temperature calcination, an additional 15% LiNO 3 .
[0057] II. The silk fibroin obtained in step (1) was dissolved in the LLZO precursor salt solution, and the silk fibroin concentration was controlled to be 3%. To accelerate the gelation of silk fibroin, an ultrasonic cell disruptor was used to ultrasonicate the silk fibroin-ceramic precursor solution at a power of 200 W for 20 minutes, and the solution was allowed to stand for 12 hours to obtain a "silk fibroin-ceramic precursor salt" hydrogel.
[0058] (3) Preparation of oxide-type porous ceramics:
[0059] Ⅰ. The "silk fibroin-ceramic precursor salt" hydrogel obtained in step (2) is placed in an oven and dried at 80° C. for 24 hours to obtain a dry gel.
[0060] Ⅱ. The dry gel was placed in a tubular furnace and calcined at 850°C for 2 h under air conditions to obtain oxide-type LLZO porous ceramics.
[0061] Scanning electron microscope (SEM) images of oxide-type LLZO porous ceramics are shown in Figure 1 .
[0062] (4) Preparation of oxide-type porous ceramic composite solid electrolyte:
[0063] Ⅰ. 2.45 g PEO and 0.8 g LiTFSI were vacuum dried at 50° C. and 100° C. for 24 h, respectively, and then dissolved in 50 mL acetonitrile, and the oxide-type LLZO porous ceramic obtained in step (3) was added, wherein the oxide-type LLZO porous ceramic accounted for 10% of the total amount of PEO, LiTFSI and oxide-type LLZO porous ceramic. Finally, the mixed solution was stirred and dispersed evenly to form a solid electrolyte mixed solution.
[0064] II. The solid electrolyte mixed solution was coated on a polytetrafluoroethylene mold. After the acetonitrile was completely volatilized, the composite solid electrolyte membrane was separated from the mold and vacuum dried at 50 °C for 24 h to remove the residual acetonitrile and adsorbed H 2 O, and obtain the oxide-type LLZO porous ceramic composite solid electrolyte.
[0065] Example 2
[0066] A method for preparing a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, the method comprising the following specific steps:
[0067] (1) Preparation of silk fibroin:
[0068] Ⅰ. Add 2.5g Na 2 CO 3 The mixture was dissolved in 500 mL of deionized water, and then 10 g of silk cocoons were added. The mixture was degummed in a 98°C water bath for 30 min. The degumming was repeated three times to obtain silk fibroin fibers.
[0069] Ⅱ. Press CaCl 2 :CH 3 CH 2 OH:H 2 The silk fibroin solution was prepared in a molar ratio of O=1:2:8, and then the silk fibroin fibers were placed in the solution and dissolved in a water bath at 75°C for 4 hours to obtain the silk fibroin solution.
[0070] III. The silk fibroin solution was centrifuged and dialyzed for 72 hours to remove impurities and residual metal ions, and then the purified silk fibroin solution was placed in a refrigerator for 24 hours, and finally freeze-dried at -50°C and 40Pa for 72 hours to obtain silk fibroin protein.
[0071] (2) Preparation of “Silk Fibroin-Oxide Ceramic Precursor Salt” Hydrogel:
[0072] Ⅰ. 15.7 mmol LiNO 3 , 0.6 mmolAl(NO 3 ) 3 9H 2 O,7.5 mmol La(NO 3 ) 3 6H 2 O, 5mmol ZrO(NO 3 ) 3 6H 2 O was dissolved in 15 mL of deionized water to obtain the oxide ceramic Li 6.28 Al 0.24 La 3 Zr 2 O 12 (LALZO) precursor salt solution, in order to compensate for the lithium loss in LALZO during subsequent high temperature calcination, an additional 15% LiNO 3 .
[0073] II. The silk fibroin obtained in step (1) was dissolved in the LALZO precursor salt solution, and the silk fibroin concentration was controlled to be 5%. To accelerate the gelation of silk fibroin, an ultrasonic cell disruptor was used to ultrasonicate the silk fibroin-ceramic precursor solution at a power of 400 W for 10 min, and the solution was allowed to stand for 12 h to obtain a "silk fibroin-ceramic precursor salt" hydrogel.
[0074] (3) Preparation of oxide-type porous ceramics:
[0075] Ⅰ. The "silk fibroin-ceramic precursor salt" hydrogel obtained in step (2) is placed in an oven and dried at 80° C. for 24 hours to obtain a dry gel.
[0076] Ⅱ. The dry gel was placed in a tubular furnace and calcined at 850°C for 2 h under air conditions to obtain oxide-type LALZO porous ceramics.
[0077] (4) Preparation of oxide-type porous ceramic composite solid electrolyte:
[0078] Ⅰ. 2.45 g PEO and 0.8 g LiTFSI were vacuum dried at 50° C. and 100° C. for 24 h, respectively. Then, the two were dissolved in 50 mL acetonitrile, and the oxide-type LALZO porous ceramic obtained in step (3) was added, wherein the oxide-type LALZO porous ceramic accounted for 0%, 5%, 10%, 15%, and 20% of the total amount of PEO, LiTFSI, and oxide-type LALZO porous ceramic, respectively. Finally, the mixed solution was stirred and dispersed evenly to form a solid electrolyte mixed solution.
[0079] II. The solid electrolyte mixed solution was coated on a polytetrafluoroethylene mold. After the acetonitrile was completely volatilized, the composite solid electrolyte membrane was separated from the mold and vacuum dried at 50 °C for 24 h to remove the residual acetonitrile and adsorbed H 2 O, and obtain the oxide-type LALZO porous ceramic composite solid electrolyte.
[0080] The surface SEM images of LALZO porous ceramic composite solid electrolytes with different contents of oxide and the cross-sectional SEM images of LALZO porous ceramic composite solid electrolytes with 10% content of oxide are shown in Figure 2 .
[0081] Example 3
[0082] A method for preparing a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, the method comprising the following specific steps:
[0083] (1) Preparation of silk fibroin:
[0084] Ⅰ. Add 2.5g Na 2 CO 3 The mixture was dissolved in 500 mL of deionized water, and then 10 g of silk cocoons were added. The mixture was degummed in a 98°C water bath for 30 min. The degumming was repeated three times to obtain silk fibroin fibers.
[0085] Ⅱ. Press CaCl 2 :CH 3 CH 2 OH:H 2The silk fibroin solution was prepared in a molar ratio of O=1:2:8, and then the silk fibroin fibers were placed in the solution and dissolved in a water bath at 75°C for 4 hours to obtain the silk fibroin solution.
[0086] III. The silk fibroin solution was centrifuged and dialyzed for 72 hours to remove impurities and residual metal ions, and then the purified silk fibroin solution was placed in a refrigerator for 24 hours, and finally freeze-dried at -50°C and 40Pa for 72 hours to obtain silk fibroin protein.
[0087] (2) Preparation of “Silk Fibroin-Oxide Ceramic Precursor Salt” Hydrogel:
[0088] Ⅰ. 15.7 mmol LiNO 3 , 0.6 mmolAl(NO 3 ) 3 9H 2 O,7.5 mmol La(NO 3 ) 3 6H 2 O, 5mmol ZrO(NO 3 ) 3 6H 2 O was dissolved in 15 mL of deionized water to obtain the oxide ceramic Li 6.28 Al 0.24 La 3 Zr 2 O 12 (LALZO) precursor salt solution, in order to compensate for the lithium loss in LALZO during subsequent high temperature calcination, an additional 15% LiNO 3 .
[0089] II. The silk fibroin obtained in step (1) was dissolved in the LALZO precursor salt solution, and the silk fibroin concentration was controlled to be 5%. To accelerate the gelation of silk fibroin, an ultrasonic cell disruptor was used to ultrasonicate the silk fibroin-ceramic precursor solution at a power of 300 W for 15 minutes, and the solution was allowed to stand for 12 hours to obtain a "silk fibroin-ceramic precursor salt" hydrogel.
[0090] (3) Preparation of oxide-type porous ceramics:
[0091] Ⅰ. The "silk fibroin-ceramic precursor salt" hydrogel obtained in step (2) is placed in an oven and dried at 80° C. for 24 hours to obtain a dry gel.
[0092] Ⅱ. The dry gel was placed in a tubular furnace and calcined at 900°C for 2 h under air conditions to obtain oxide-type LALZO porous ceramics.
[0093] The X-ray electron diffraction (XRD) pattern of oxide-type LALZO porous ceramics is shown in Figure 3; High-power transmission electron microscopy (HRTEM) images and selected area electron diffraction (SAED) patterns are shown in Figure 4 .
[0094] (4) Preparation of oxide-type porous ceramic composite solid electrolyte:
[0095] Ⅰ. 2.4 g PVDF and 0.8 g LiTFSI were vacuum dried at 50° C. and 100° C. for 24 h, respectively, and then dissolved in 50 mL acetonitrile, and the oxide-type LALZO porous ceramic obtained in step (3) was added, wherein the oxide-type LALZO porous ceramic accounted for 10% of the total amount of PVDF, LiTFSI and oxide-type LALZO porous ceramic. Finally, the mixed solution was stirred and dispersed evenly to form a solid electrolyte mixed solution.
[0096] II. The solid electrolyte mixed solution was coated on a polytetrafluoroethylene mold. After the acetonitrile was completely volatilized, the composite solid electrolyte membrane was separated from the mold and vacuum dried at 50 °C for 24 h to remove the residual acetonitrile and adsorbed H 2 O, and obtain the oxide-type LALZO porous ceramic composite solid electrolyte.
[0097] Example 4
[0098] A method for preparing a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, the method comprising the following specific steps:
[0099] (1) Preparation of silk fibroin:
[0100] Ⅰ. Add 2.5g Na 2 CO 3 The mixture was dissolved in 500 mL of deionized water, and then 10 g of silk cocoons were added. The mixture was degummed in a 98°C water bath for 30 min. The degumming was repeated three times to obtain silk fibroin fibers.
[0101] Ⅱ. Press CaCl 2 :CH 3 CH 2 OH:H 2 The silk fibroin solution was prepared in a molar ratio of O=1:2:8, and then the silk fibroin fibers were placed in the solution and dissolved in a water bath at 75°C for 4 hours to obtain the silk fibroin solution.
[0102] III. The silk fibroin solution was centrifuged and dialyzed for 72 hours to remove impurities and residual metal ions, and then the purified silk fibroin solution was placed in a refrigerator for 24 hours, and finally freeze-dried at -50°C and 40Pa for 72 hours to obtain silk fibroin protein.
[0103] (2) Preparation of “Silk Fibroin-Oxide Ceramic Precursor Salt” Hydrogel:
[0104] Ⅰ. 15.36 mmol LiNO 3 , 7.5 mmol La(NO 3 ) 3 6H 2 O, 3.5 mmol ZrO(NO 3 ) 3 6H 2 O, 1.5 mmol TaO(NO 3 ) 3 Dissolve in 15 mL of deionized water to obtain the oxide ceramic Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO) precursor salt solution, in order to compensate for the lithium loss in LLZTO during subsequent high temperature calcination, an additional 15% LiNO 3 .
[0105] II. The silk fibroin obtained in step (1) was dissolved in the LLZTO precursor salt solution, and the silk fibroin concentration was controlled to be 7%. To accelerate the gelation of silk fibroin, an ultrasonic cell disruptor was used to ultrasonicate the silk fibroin-ceramic precursor solution at a power of 350 W for 12 minutes, and the solution was allowed to stand for 12 hours to obtain a "silk fibroin-ceramic precursor salt" hydrogel.
[0106] (3) Preparation of oxide-type porous ceramics:
[0107] Ⅰ. The "silk fibroin-ceramic precursor salt" hydrogel obtained in step (2) is placed in an oven and dried at 80° C. for 24 hours to obtain a dry gel.
[0108] Ⅱ. The dry gel was placed in a tubular furnace and calcined at 900°C for 2 h under air conditions to obtain oxide-type LLZTO porous ceramics.
[0109] (4) Preparation of oxide-type porous ceramic composite solid electrolyte:
[0110] Ⅰ. 2.4 g PVDF and 0.8 g LiTFSI were vacuum dried at 50°C and 100°C for 24 h, respectively, and then dissolved in 50 mL acetonitrile, and the oxide-type LLZTO porous ceramic obtained in step (3) was added, wherein the oxide-type LLZTO porous ceramic accounted for 10% of the total amount of PVDF, LiTFSI and oxide-type LLZTO porous ceramic. Finally, the mixed solution was stirred and dispersed evenly to form a solid electrolyte mixed solution.
[0111] II. The solid electrolyte mixed solution was coated on a polytetrafluoroethylene mold. After the acetonitrile was completely volatilized, the composite solid electrolyte membrane was separated from the mold and vacuum dried at 50 °C for 24 h to remove the residual acetonitrile and adsorbed H 2 O, and obtain the oxide-type LLZTO porous ceramic composite solid electrolyte.
[0112] The electrochemical impedance spectrum (EIS) of the stainless steel / solid electrolyte / stainless steel symmetric cell of the oxide-type LLZTO porous ceramic composite solid electrolyte prepared in this example is shown in Figure 5 ; The cycling performance of Li / solid electrolyte / Li symmetric battery is shown in Figure 6 .
[0113] Example 5
[0114] A method for preparing a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, the method comprising the following specific steps:
[0115] (1) Preparation of silk fibroin:
[0116] Ⅰ. Add 2.5g Na 2 CO 3 The mixture was dissolved in 500 mL of deionized water, and then 10 g of silk cocoons were added. The mixture was degummed in a 98°C water bath for 30 min. The degumming was repeated three times to obtain silk fibroin fibers.
[0117] Ⅱ. Press CaCl 2 :CH 3 CH 2 OH:H 2 The silk fibroin solution was prepared in a molar ratio of O=1:2:8, and then the silk fibroin fibers were placed in the solution and dissolved in a water bath at 75°C for 4 hours to obtain the silk fibroin solution.
[0118] III. The silk fibroin solution was centrifuged and dialyzed for 72 hours to remove impurities and residual metal ions, and then the purified silk fibroin solution was placed in a refrigerator for 24 hours, and finally freeze-dried at -50°C and 40Pa for 72 hours to obtain silk fibroin protein.
[0119] (2) Preparation of “Silk Fibroin-Oxide Ceramic Precursor Salt” Hydrogel:
[0120] Ⅰ. 4.62 mmol LiNO 3 , 7.78 mmol La(NO 3 ) 3 6H 2 O, 14 mmol Ti(OC 4 H 9 ) 4 Dissolve in 15 mL of deionized water to obtain the oxide ceramic Li3x La (2 / 3)-x TiO 3 (LLTO) precursor salt solution, in order to compensate for the lithium loss in LLTO during subsequent high temperature calcination, an additional 15% LiNO 3 .
[0121] II. The silk fibroin obtained in step (1) was dissolved in the LLTO precursor salt solution, and the silk fibroin concentration was controlled to be 7%. To accelerate the gelation of silk fibroin, an ultrasonic cell disruptor was used to ultrasonicate the silk fibroin-ceramic precursor solution at a power of 350 W for 12 minutes, and the solution was allowed to stand for 12 hours to obtain a "silk fibroin-ceramic precursor salt" hydrogel.
[0122] (3) Preparation of oxide-type porous ceramics:
[0123] Ⅰ. The "silk fibroin-ceramic precursor salt" hydrogel obtained in step (2) is placed in an oven and dried at 80° C. for 24 hours to obtain a dry gel.
[0124] Ⅱ. The dry gel was placed in a tubular furnace and calcined at 900°C for 2 h under air conditions to obtain oxide-type LLTO porous ceramics.
[0125] (4) Preparation of oxide-type porous ceramic composite solid electrolyte:
[0126] Ⅰ. Mix 2.4g PMMA and 0.8g LiClO 4 The mixture was vacuum dried at 50°C and 100°C for 24 h, and then the two were dissolved in 50 mL of acetonitrile, and the oxide-type LLTO porous ceramic obtained in step (3) was added, wherein the oxide-type LLTO porous ceramic accounted for 1.3% of PMMA, 1.2% of LiClO, and 1.3% of PMMA. 4 , and oxide-type LLTO porous ceramics account for 10% of the total amount of the three. Finally, the mixed solution is stirred and dispersed evenly to form a solid electrolyte mixed solution.
[0127] II. The solid electrolyte mixed solution was coated on a polytetrafluoroethylene mold. After the acetonitrile was completely volatilized, the composite solid electrolyte membrane was separated from the mold and vacuum dried at 50 °C for 24 h to remove the residual acetonitrile and adsorbed H 2 O, and obtain the oxide-type LLTO porous ceramic composite solid electrolyte.
[0128] The Li / solid electrolyte / LiFePO of the oxide-type LLTO porous ceramic composite solid electrolyte prepared in this embodiment 4 The long-term cycle performance of all-solid-state batteries is shown in Figure 7 .
[0129] The SEM image of the oxide-type LLZO porous ceramics prepared in Example 1 is as follows: Figure 1As shown in Figure 2, the LLZO porous ceramic framework is composed of a plurality of garnet ceramic branches connected to each other to form a sheet-like structure, which not only avoids the aggregation of ceramic fillers in the composite solid electrolyte, but also provides a good foundation for the Li + It provides a continuous and fast transmission path, which helps to improve the ionic conductivity of the electrolyte. In addition, there are many pores in the LLZO sheet ceramic framework, which is conducive to the subsequent "polymer-conductive lithium salt" solution to fully penetrate into the porous ceramic network, forming a tight ceramic / polymer interface to improve the ion conduction rate at the interface and reduce the interface resistance between the two.
[0130] The surface SEM photos of the oxide-type LALZO porous ceramic composite solid electrolytes with different contents prepared in Example 2 and the cross-sectional SEM photos of the oxide-type LALZO porous ceramic composite solid electrolytes with 10% content are shown in FIG. Figure 2 As shown. Figure 2 It can be seen from the SEM that with the increase of the porous ceramic content, the surface of the composite electrolyte gradually becomes rough from smooth. Without the addition of ceramic fillers, the surface of the polymer electrolyte is smooth and flat. With the continuous addition of oxide porous ceramic fillers, the surface of the composite solid electrolyte gradually becomes rough from smooth, which not only affects the overall ionic conductivity of the electrolyte, but also causes the electrolyte / electrode interface resistance to increase in all-solid-state lithium batteries, which is extremely unfavorable for the overall electrochemical performance of the battery. Therefore, the preferred oxide porous ceramic content is 10%. The cross-sectional SEM photo shows that the thickness of the composite solid electrolyte is about 100μm.
[0131] The X-ray electron diffraction (XRD) pattern of the oxide-type LALZO porous ceramic prepared in Example 3 is as follows: Figure 3 The diffraction peaks in the XRD spectrum are basically consistent with the standard cubic phase garnet crystal Li 5 La 3 Nb 2 O 12 The results are consistent (PDF card no.45-0109), indicating that cubic garnet LLZO was successfully prepared. In addition, there are trace impurity peaks in the XRD spectrum, which are attributed to La formed by lithium volatilization during high temperature sintering. 2 Zr 2 O 7 .
[0132] The high magnification transmission electron microscope (HRTEM) image and selected area electron diffraction (SAED) spectrum of the oxide-type LALZO porous ceramic prepared in Example 3 are as follows: Figure 4As shown. The HRTEM image shows clear lattice fringes, and the lattice spacing is measured to be 0.52 and 0.26 nm, corresponding to the (211) and (422) crystal planes of standard garnet LLZO, respectively, further indicating that pure LLZO ceramics have been successfully prepared. The SAED spectrum shows a series of concentric derivative rings, which are attributed to the polycrystalline structure of LLZO porous ceramics.
[0133] The electrochemical impedance spectrum (EIS) of the stainless steel / solid electrolyte / stainless steel symmetric cell of the oxide-type LLZTO porous ceramic composite solid electrolyte prepared in Example 4 is shown in FIG. Figure 5 As shown. By calculation, it is found that the ionic conductivity of the composite solid electrolyte at 30°C is as high as 7.49×10 -5 S cm -1 The high ionic conductivity mainly comes from two reasons: first, the oxide-type porous ceramics as active fillers have high ionic conductivity and form a continuous 3D ion-conducting framework, which accelerates Li + transmission; secondly, the ceramic filler reduces the crystallinity of the polymer and accelerates the movement of the polymer chain segments, making Li + Easier to migrate in polymer matrix.
[0134] The cycle performance of the Li / solid electrolyte / Li symmetric battery of the oxide-type LLZTO porous ceramic composite solid electrolyte prepared in Example 4 is shown in FIG. Figure 6 The voltage fluctuation of the symmetrical lithium battery is very small, with almost no obvious change, always maintained at around 0.14V, and can be stably cycled for more than 250h. This shows that Li + It can be orderly transferred inside the composite solid electrolyte and uniformly deposited at the interface, thus forming a stable solid electrolyte / lithium metal interface layer.
[0135] Li / solid electrolyte / LiFePO of the oxide-type LLTO porous ceramic composite solid electrolyte prepared in Example 5 4 The long-term cycle performance of all-solid-state batteries is shown in Figure 2. Figure 7 After 380 cycles, the all-solid-state battery still has 123 mAh g -1 It has a high discharge capacity, a capacity decay of only 0.067% per cycle, and an average coulombic efficiency of more than 99%, with excellent cycle stability.
[0136] The above-mentioned embodiments prepare different types of oxide porous ceramics, including garnet-type and perovskite-type ceramics. Therefore, the method of preparing porous ceramics using silk fibroin hydrogel in the present invention is suitable for deriving various types of oxide porous ceramics.
[0137] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A method for preparing a silk fibroin hydrogel-derived oxide-type porous ceramic composite solid electrolyte, characterized in that The method comprises the following steps: S1. Preparation of "Silk Fibroin-Oxide Ceramic Precursor Salt" Hydrogel: dissolving an oxide ceramic precursor salt in water to obtain a ceramic precursor salt solution; Then, the silk fibroin is dissolved in a ceramic precursor salt solution to obtain a "silk fibroin-oxide ceramic precursor salt" aqueous solution with a silk fibroin mass content of 3%-10%, and the solution is subjected to ultrasonic treatment and allowed to stand to obtain a "silk fibroin-oxide ceramic precursor salt" hydrogel; S2. Preparation of oxide-type porous ceramics: The "silk fibroin-oxide ceramic precursor salt" hydrogel obtained in S1 is dried to obtain a xerogel, which is then calcined in air to obtain an oxide-type porous ceramic; S3. Preparation of oxide-type porous ceramic composite solid electrolyte: The polymer that can be used as a solid electrolyte and the conductive lithium salt are vacuum dried in a temperature range below their respective melting points for later use; Then the polymer and the conductive lithium salt are dissolved in acetonitrile, and the oxide-type porous ceramic obtained by S2 is added, stirred and dispersed evenly to form a solid electrolyte mixed solution; the weight ratio of the polymer to the conductive lithium salt is 2 to 4:1; the oxide-type porous ceramic accounts for 5% to 30% of the total weight of the polymer, the conductive lithium salt and the oxide-type porous ceramic; Finally, the solid electrolyte mixed solution is coated on the mold, and after the acetonitrile is completely volatilized, the mold is demoulded and vacuum dried to obtain an oxide-type porous ceramic composite solid electrolyte.
2. The preparation method according to claim 1, characterized in that: The ceramic precursor salt in S1 is selected from garnet type, NASICON type, perovskite type or antiperovskite type ceramic precursor salt, and the content of the ceramic precursor salt in the "silk fibroin-oxide ceramic precursor salt" aqueous solution is 0.04-0.8 mol / L.
3. The preparation method according to claim 1, characterized in that: The parameters of the ultrasonic treatment in S1 are: ultrasonic power of 200-500 W, ultrasonic time of 5-20 min, and standing time after ultrasonic treatment of 6-48 h.
4. The preparation method according to claim 1, characterized in that: The drying temperature of the "silk fibroin-oxide ceramic precursor salt" hydrogel in S2 is 80°C±5°C, and the drying time is 24h±4h.
5. The preparation method according to claim 1, characterized in that: The calcination temperature of the "silk fibroin-oxide ceramic precursor salt" dry gel in S2 is 700-1000°C, and the calcination time is 2h±0.5h.
6. The preparation method according to claim 1, characterized in that: In S3, the oxide-type porous ceramic accounts for 10% of the total weight of the polymer, the conductive lithium salt and the oxide-type porous ceramic; the concentration of the polymer in the mixed solution is 0.02-0.1 g / L.
7. The preparation method according to claim 1, characterized in that: In S3, The polymer is selected from a mixture of one or more polymers selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinyl chloride (PVC), The conductive lithium salt is selected from lithium halides (LiX, X=F, Cl, Br, I), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4).
8. The preparation method according to claim 1, characterized in that: The vacuum drying temperature of the oxide-type porous ceramic composite solid electrolyte in S3 is 50°C±5°C, and the drying time is 24h±4h.
9. The preparation method according to claim 1, characterized in that The preparation method of the silk fibroin comprises the following steps: degumming and refining silk cocoons to obtain pure silk fibroin, dissolving salt to obtain a silk fibroin solution, and centrifuging, dialysis and freeze drying to obtain the silk fibroin.
10. An oxide-type porous ceramic composite solid electrolyte for a flexible solid-state lithium battery, wherein the composite material is prepared by the preparation method according to claim 1.